Patenting Race: The Problems Of Ethnic Genetic Testing Patents - Price, W. Nicholson; Price, W. Nicholson (Science and Technology Law Review, 2007)
Genetic tests which target specific ethnicities are fraught with problems, and will become commonplace unless action is taken to stop them. The first has already been patented in Europe by the U.S. company Myriad Genetics, despite vigorous opposition. Myriad’s patent covers testing for a mutation in the breast cancer gene BRCA2 in Ashkenazi-Jewish women. The patenting and approval of BiDil, a heart medication for African-Americans, provides strong evidence that patenting ethnically based medicine has become more acceptable in the United States. In allowing race-based drugs, the United States is much closer to allowing ethnic genetic testing, which has deeper, more insidious, and more widespread negative effects. As such, action must be taken to avoid the patenting of ethnic genetic tests. While existing anti-discrimination law may provide one reactive means to challenge these tests, its extent is unclear, and that route is slow and uncertain. Instead, Congress should proactively enact narrow legislation specifically tailored to prohibit these tests.